Comparison of Frozen Embryo Transfer Outcomes Between Uterine Infusion of Granulocyte Colony-Stimulating Factor and Growth Hormone Application in Patients With Thin Endometrium: A Retrospective Study - Jiang, Lei; Xu, Xin; Cao, Ziyu; Yang, Ni; Wang, Shaoqing; Wang, Luning; Xu, Xiuhua; Li, Qian; Shi, Baojun; Hao, Guimin (Frontiers in Endocrinology, 2021)
[Abstract] OBJECTIVE: To investigate the effect of two treatments on the outcome of freeze-thaw embryo transfer for pregnancy assistance in thin endometrium. METHODS: A retrospective study was conducted on 66 patients who failed in the first cycle treated in the reproductive medicine center of the Second Hospital of Hebei Medical University from January 2018 to December 2019, granulocyte colony stimulating factor (G-CSF) was used through cavity infusion in one group（n=25）, and growth hormone (GH) was subcutaneous injected in another group（n=41）. The clinical data of the two groups were compared, including morphology and thickness of endometrium, biochemical pregnancy rate, clinical pregnancy rate, implantation rate, miscarriage rate and live birth rate in each period of hormone replacement cycle. RESULTS: There was no significant difference in age, BMI, AMH, FSH, LH, E2,infertility years, number of transferred embryos, basal endometrium and thickness of endometrium on the day of P administration before and after treatment (P> 0.05).After treatment, compared to GH group, G-CSF group presented higher biochemical pregnancy rate (56% versus 48.8%; P=0.569), clinical pregnancy rate (52% versus 46.3%; P=0.655 ), implantation rate (34.8% versus 27.5%; P=0.391) and live birth rate (40% versus 31.7%; P=0.493), but the differences were not statistically significant (P＞0.05).On the 5th day of treatment, the endometrial thickness in G-CSF group was thinner than that in GH group (4.83±0.85 versus5.75±1.27；P< 0.05), but it had no correlation with pregnancy outcome (P > 0.05). There was no significant difference in endometrial thickness between the two groups on the 7th, 9th day of treatment and the day of P administration (P > 0.05). On the 5th day of treatment, the proportion of endometrial type A morphology in GH group was significantly higher than that in G-CSF group (P < 0.05 ), while the type B morphology in G-CSF group was significantly higher than that in GH group (P< 0.05 ). CONCLUSION: Although G-CSF and GH may not have a role in increasing endometrium, both of them can improve the pregnancy outcomes of patients with thin endometrium in FET cycle. And the effects of the two treatments were similar.